Effect of Supplementation of L- Threonine on Growth Performance and Carcass Characteristics in Japanese Quail - Namdeo, Pramod; Tiwari, S P; Doneria, Raina; Dubey, Meenu; Yadav, Rajkumar (Indian Journal of Animal Nutrition, 2019)
Day old Japanese quail chicks (n = 150) were randomly allocated to 5 groups with three replicates of 10 birds in each. Five types of diets were prepared containing 24, 23, 22, 21 and 20 % crude protein for group T1 to T5 respectively. L-threonine was supplemented in the diet @ 0.0 %, 0.05%, 0.1%, 0.15% and 0.2% from group T1- T5 respectively. Body weight at 28 d was significantly (P<0.01) high in group T3 as compare to other groups. The feed intake differs non significantly amongst the group. Â The FCR was better in group T3 where threonine was supplemented @ 0.1% in the diet. Supplementation of threonine resulted in significant increase in the weight of thigh however other carcass traits differ non significantly amongst the treatment groups It is concluded that Japanese quail can be raised in lower CP diet (22%) with 0.1% threonine supplementation to achieve better performance